Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1063/1.2919806
|View full text |Cite
|
Sign up to set email alerts
|

A model of diffusion in a potential well for the dynamics of the large-scale circulation in turbulent Rayleigh–Bénard convection

Abstract: Experimental measurements of properties of the large-scale circulation (LSC) in turbulent convection of a fluid heated from below in a cylindrical container of aspect ratio one are presented and used to test a model of diffusion in a potential well for the LSC. The model consists of a pair of stochastic ordinary differential equations motivated by the Navier-Stokes equations. The two coupled equations are for the azimuthal orientation θ 0 , and for the azimuthal temperature amplitude δ at the horizontal midpla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
185
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(206 citation statements)
references
References 45 publications
(132 reference statements)
16
185
5
Order By: Relevance
“…Broadly, these works involve either stochasticity (e.g., "stochastic resonance" [8,13]), or low-dimensional models with noise [14,15]. Mishra et al [10] studied the large-scale modes of RBC in a cylindrical geometry and showed that the dipolar mode decreases in amplitude and the quadrupolar mode increases during the cessation-led reversals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Broadly, these works involve either stochasticity (e.g., "stochastic resonance" [8,13]), or low-dimensional models with noise [14,15]. Mishra et al [10] studied the large-scale modes of RBC in a cylindrical geometry and showed that the dipolar mode decreases in amplitude and the quadrupolar mode increases during the cessation-led reversals.…”
mentioning
confidence: 99%
“…Broadly, these works involve either stochasticity (e.g., "stochastic resonance" [8, 13]), or low-dimensional models with noise [14,15]. Mishra et al…”
mentioning
confidence: 99%
“…Recent studies also report that the LSC flow-reversals and its tilted orientation are strongly influenced by the corner-flows that form in a rectangular geometry [12]. The dynamics of a nearly-vertical, single LSC can be modeled by a set of nonlinear stochastic differential equations that describe the amplitude of azimuthal temperature variations, δ, and the azimuthal orientation angle, θ 0 [13,14]. This model is found to be in excellent agreement with the typical fluctuations of the LSC [13,14].…”
mentioning
confidence: 99%
“…The dynamics of a nearly-vertical, single LSC can be modeled by a set of nonlinear stochastic differential equations that describe the amplitude of azimuthal temperature variations, δ, and the azimuthal orientation angle, θ 0 [13,14]. This model is found to be in excellent agreement with the typical fluctuations of the LSC [13,14]. Yet, the cessations require an extension of the model, since boundary terms describing the thermal and viscous diffusion become dominant terms when the amplitudes are small, as they inevitably must be during a cessation.…”
mentioning
confidence: 99%
“…This ordering influence stops when the large-scale circulation decelerates strongly and becomes re-oriented. Such events have been studied statistically in experiments [27][28][29], numerically in two-dimensional [24,30,31] or three-dimensional [32] convection as well as in low-dimensional models [33].…”
Section: Plume Collision Due To Transition Of Large-scale Flowmentioning
confidence: 99%